Ijbar Dalam Konteks Kekinian: Telaah Pemahaman KH. Husein Muhammad - Isyrofah Tazkiyah Iroyna (Sekolah Tinggi Agama Islam Negeri Majene, 2024)
According to the madzhab scholars, the right of ijbar aims to provide protection to women from miscreants by involving the mujbir wali in selescting a couple. However, over time, ijbar has been perspective by some people as the right to force marriage. Unlike the previous interpretation, Kiai Husein interprets the right of ijbar as the right to marry or direct. This study aims to find out the legal basis of KH. Husein in interpreting the right of ijbar and its legal impact in the current Indonesian context. This research is normative research or library research, with an istislahi approach using Imam Al-Ghazali's maslahah mursalah theory. KH. Husein reinterpreted the concept of ijbar by reviewing at the five pillars of the objectives of Islamic law which were then expanded by aiming at human rights values and equal relations between men and women. Based on this legal basis, Kiai Husein's interpretation of ijbar is different from previous interpretations which interpret the right to force into the right to marry or direct. In that way, ijbar as the right to marry no longer limits women's rights to determine a partner. With this interpretation, it can be seen that KH. Husein prioritises the maslahah aspect in determining a law. KH. Husein also connects the relationship between children and parents without limiting the rights between the two in requiring the concept of ijbar. KH. Husein's interpretation of ijbar rights has a close relevance to the current conditions of Indonesian people.